2022
DOI: 10.1039/d1ta07903d
|View full text |Cite
|
Sign up to set email alerts
|

A polyoxometalate cluster-based single-atom catalyst for NH3 synthesis via an enzymatic mechanism

Abstract: NH3 synthesis by electrochemical N2 reduction reaction (eNRR) under mild conditions has attracted much attention. Here, by means of first principles calculations, we propose a new strategy using a transition...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 89 publications
0
21
0
Order By: Relevance
“…The catalyst is considered to be the best catalyst for HER in which DGÃ H tends to its ideal value DGÃ H ffi 0 ð Þleading to the desorption of hydrogen easily from the catalyst surface either through the Tafel or the Heyrovsky step, which in turn, leaves the catalyst surface prepared for the successive adsorption of hydrogen for further reaction to proceed. 38 Here, the values of DGÃ H , as shown in the Fig. 2(d), vary from À0.2 eV to À0.79 eV which indicates that the H binds strongly with the catalyst surface that hinders the HER to proceed further.…”
Section: Resultsmentioning
confidence: 78%
“…The catalyst is considered to be the best catalyst for HER in which DGÃ H tends to its ideal value DGÃ H ffi 0 ð Þleading to the desorption of hydrogen easily from the catalyst surface either through the Tafel or the Heyrovsky step, which in turn, leaves the catalyst surface prepared for the successive adsorption of hydrogen for further reaction to proceed. 38 Here, the values of DGÃ H , as shown in the Fig. 2(d), vary from À0.2 eV to À0.79 eV which indicates that the H binds strongly with the catalyst surface that hinders the HER to proceed further.…”
Section: Resultsmentioning
confidence: 78%
“…In the chemistry of group 6 polyoxometalates, the polyoxomolybdates are significantly more labile than the polyoxotungstates, thus making researchers favor the latter in their studies of POM chemistry. However, several studies of polyoxomolybdates’ reactivity [ 39 ] and catalytic performance (electron transfer reactions) appeared [ 40 , 41 , 42 , 43 , 44 , 45 ]. One of the central complexes in this chemistry is (Bu 4 N) 4 [β-Mo 8 O 26 ] ( Scheme 1 ), which is a standard precursor of all reactions in organic media, leading to a huge number of materials with different properties [ 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, selectivity analyses indicated that HER may exceed NRR on the small cluster, whereas NH 3 could have been synthesized selectively on the Ni 13 –TiO 2 (101) catalyst. Recently, Talib et al proposed that a phosphomolybdic acid (PMA) cluster, consisting of a central PO 4 tetrahedral core connected with 12 MoO 6 octahedral units can anchor TM atoms to develop suitable heterogeneous SACs for NRR. Among a series of 3d, 4d, and 5d TMs, the authors found that Mo/PMA has a superior electrocatalytic effect over others.…”
Section: Single-atom/cluster-decorated Metal-based Electrocatalystsmentioning
confidence: 99%